Effects and mechanisms of ginseng and ginsenosides on cognition. (25th March 2014) - Smith, Imogen; Williamson, Elizabeth M; Putnam, Sophie; Farrimond, Jonathan; Whalley, Benjamin J
<x xml:space="preserve">Abstract</x> Reviewed here is the existing evidence for the effects of ginseng extracts and isolated ginsenosides relevant to cognition in humans. Clinical studies in healthy volunteers and in patients with neurological disease or deficit, evidence from preclinical models of cognition, and pharmacokinetic data are considered. Conditions under which disease modification may indirectly benefit cognition but may not translate to cognitive benefits in healthy subjects are discussed. The number of chronic studies of ginseng effects in healthy individuals is limited, and the results from acute studies are inconsistent, making overall assessment of ginseng's efficacy as a cognitive enhancer premature. However, mechanistic results are encouraging; in particular, the ginsenosides Rg3, Rh1, Rh2, Rb1, Rd, Rg2, and Rb3, along with the aglycones protopanaxadiol and protopanaxatriol, warrant further attention. Compound K has a promising pharmacokinetic profile and can affect neurotransmission and neuroprotection. Properly conducted trials using standardized tests in healthy individuals reflecting the target population for ginseng supplementation are required to address inconsistencies in results from acute studies. The evidence summarized here suggests ginseng has potential, but unproven, benefits on cognition.